PERKAWINAN MEMPELAI WANITA YANG TIDAK MENGGUNAKAN WALI NASAB DALAM ADAT KEJAWEN - NIM. A1011201029, ZANIBA ARIFA ABSYACH (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractMarriage is a physical and spiritual bond between a man and a woman in a relationship that is valid in the eyes of law and religion. Marriage in Indonesia is regulated by statutory provisions, Islamic law and customary law. In Javanese tradition, there is a tradition of calculating the weton before a marriage takes place. They believe that this weton calculation can determine a couple's compatibility and predict future married life. There are several marriage prohibitions related to weton calculations. Because in calculating the weton of a couple there are wetons that are not suitable and are related to the prohibitions on marriage in Javanese custom. Thus, the author formulates the research problem as follows